Peningkatan Keterampilan Literasi Digital dalam Pembuatan E-Book bagi Remaja di Taman Bacaan Masyarakat (TBM) Warung Pasinaon Kabupaten Semarang - Tri Suminar; Mintarsih Arbarini; Arini Dwi Cahyani; All Fine Loretha; Amin Yusuf (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Community Reading Garden (Taman Bacaan Masyarakat/TBM) Warung Pasinaon plays an important role as a literacy center for the community, especially for youth, in enhancing reading interest and literacy skills. However, youth empowerment in digital literacy still faces several challenges, such as low writing skills, limited use of technology, and a lack of interest in digital reading. This community service program aims to provide digital literacy training through e-book creation, enabling youth to write, edit, design, and publish their works digitally. The program employs the Participatory Rural Appraisal (PRA) and learning by doing methods, targeting youth from TBM Warung Pasinaon in Semarang Regency. The training consists of five stages: introduction to digital literacy, writing and editing training, e-book creation, digital publication, and evaluation and reflection. Activities are carried out through a community empowerment approach involving workshops, hands-on practice, interactive discussions, and mentoring. The results show a significant improvement in participants’ digital literacy skills, increasing from 17.56% before to 92.00% after the training. The impact is evident through the emergence of youth e-book works, growing digital reading interest, and enhanced confidence in creative expression, thereby strengthening TBM’s role as a technology-based literacy center.